On the Systematicity of Academic Philosophy. - Alvargonzález, David (Philosophical Investigations, 2021)
In this paper, I will discuss the significance of the idea of system as applied to academic philosophy. Firstly, I will distinguish systems from other types of totalities, such as sets, aggregates and structures, and then present a definition of system and analyse the basic constituent components of any system. I will subsequently apply the proposed idea of system and its internal modulations to philosophical systems to account for the different ways of understanding academic philosophy as systematic philosophy. To end, I will argue that the systematicity of academic philosophy does not necessarily imply any dogmatism, doctrinarism or metaphysical monism.